The Role of Educational Management Support in Strengthening Teachers’ Scientific Literacy and Organizational Citizenship Behavior - Alamsyah, Mashudi; Dinihari, Yulian; Amat, Asmiaty (IJORER : International Journal of Recent Educational Research, 2026)
This study aims to examine the role of educational management support in strengthening teachers’ scientific literacy and its contribution to Organizational Citizenship Behavior (OCB) in the context of Indonesian education. The study is grounded in the assumption that high teacher motivation toward scientific activities does not automatically translate into consistent academic practices without adequate organizational support. Method: A mixed methods approach with a sequential explanatory design was employed. Quantitative data were collected from 38 teachers across several regions in Indonesia using validated Likert-scale questionnaires measuring educational management support, scientific literacy, and OCB. Descriptive and inferential statistical analyses were conducted, followed by qualitative data collection through in-depth interviews with selected participants to further explain the quantitative findings. The qualitative data were analyzed using thematic analysis, and integration was carried out at the interpretation stage. Results: The findings indicate that teachers’ interest in scientific writing is very high, while their practical experience and participation in formal training remain moderate. Educational management support plays a crucial role in bridging this gap by facilitating training, mentoring, time allocation, and academic recognition. Furthermore, strong management support is associated with higher levels of teachers’ OCB, reflected in voluntary collaboration, commitment, and proactive engagement in school development. Novelty: This study contributes novel empirical evidence by integrating educational management support, teachers’ scientific literacy, and OCB within a single analytical framework, highlighting the strategic role of educational management in fostering both academic competence and positive organizational behavior among teachers.